LA ADMINISTRACIÓN ESTRATÉGICA Y LA PRODUCTIVIDAD EN LAS AGENCIAS DE VIAJES Y TURISMO - Mayurí Barrón, Jorge Vicente (2011)
The use of Strategic Management or Strategic Planning as a tool through its matrix allows this study to be applied to Travel Agencies to improve their productivity due to high competition in the market and also for the reduction of commissions from national and international airlines, and some tourism industry borrowers, forcing to improve the quality of management by travel agencies. Statistics obtained through MINCETUR (Ministry of Foreign Trade and Tourism) identified a total of 2.383 existing travel agencies in the city of Lima taking as reference 10 of the best travel agencies operating inbound tourism, domestic and international at the same time, the travel agencies are IATA Passenger Agents and sometimes operating as tour operators. Results demonstrates that 7 of 10 agencies handle strategic planning, and for this reason they came to increase productivity.